Robotics and development of Computational Thinking: A research with primary school children in Huancavelica, Peru. - Quintanilla, Cerapio; Paredes, Joaquín; Rojas Quispe, Angel Epifanio; Gewerc, Adriana; Oré rojas, Juan José (Journal of Namibian Studies)
Different pedagogical approaches use programming skills to develop students' technological knowledge in schools leading mainly to the development of theory, all of this according to a traditional teacher-to-student knowledge transfer model. The purpose of the research was to understand the development of computational thinking of a group of 14 children, aged from 6 to 9 years old and all of them in primary school, using robotics from a constructionist prospective. The research approach is qualitative, which allowed us to follow up through observations (of) the actions performed by the students; starting with very simple activities, such as disassembling and assembling the Zowi BQ robot, then performing mechanical activities related to mathematical concepts and finally robotics activities, integrating programming with LEGO-WeDo 2.0. This intervention allowed the children to understand the basic fundamentals of computational thinking as a result of three educational projects. This research shows evidence of how students are able to understand the development of computational thinking by the design of sequences in the robots programming for problem solving and integrating areas of Science, Technology, Engineering and Mathematics; as well as strengthening their communication skills and creativity.